Analysis of Shortest Path Routing for Large Multi-Hop Wireless Networks - S.Girija, Ms; S.Kayathri, Mrs; S.Meena, Ms (International Journal of Engineering and Technology, 2018)
In the concurrent system, each node avails as a packet over the network depends on the length of the node. The length of the node generated through straight line routing algorithm. The cost of routing depends on the shortest path routing algorithm. The shortest path is determined by the cost of a distance from one node to another over the network. The capacity of a network is balanced and maintained by the straight routing. The traffic and cost is balanced over the network by using the algorithms.Â Â Â